PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI, DUKUNGAN MANAJEMEN PUNCAK DAN KOMPETENSI KARYAWAN AKUNTANSI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI - Karina Fitria Febrianti; Irwan Sutirman Wahdiat; Juwenah Juwenah (Jurnal Riset Keuangan dan Akuntansi, 2021)
Accounting information System is said to be effective when information provided by the system can serve the needs of system users. Therefore, the purpose of this research is to analyze the sophistication of information technology, peak management support and employee competence accounting towards the effectiveness of accounting information system in PT. Jasa Marga (Persero) TBK Branch Palikanci-Cirebon. Where PT Jasa Marga (Persero) TBK will gradually reimburse the cash transaction system into a non-cash transaction at all toll gates. With the implementation of 100% non-cash transactions are gradually expected to help early socialization to road users. This study used a questionnaire that was distributed to 39 respondents consisting of the Finance Division, the operational Division and the Human Resources division of PT. Jasa Marga (Persero) TBK branch of Palikanci-Cirebon. This type of research is (basic research).  The data analysis methods used in this study were multiple regression analysis. The results showed that the sophistication of information technology and top management support has an effect on the effectiveness of accounting information systems, whereas accounting employee competence has no effect on the effectiveness of the system Accounting information. Keywords: Effectiveness of accounting information systems, sophistication of information technology, top management support, accounting employee Competence